13. THE RELATIONSHIP BETWEEN ANTERIOR CHAMBER DEPTH AS AN ANATOMICAL INDEX AND DEMOGRAPHIC FACTORS AND VISUAL ACUITY IN MIDDLE-AGED VIETNAMESE ADULTS (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the relationship between anterior chamber depth and demographic factors, as well as intraocular pressure, in Vietnamese adults aged 46-65 years.Subjects and methods: A cross-sectional descriptive study was conducted on 195 Vietnamese individuals aged 46-65 years, using the IOL Master 700 device at the Vietnam National Eye Hospital.Results: Among the 195 participants, 94 were male (48.2%) and 101 were female (51.7%). The mean anterior chamber depth was 3.15 ± 0.36 mm; anterior chamber depth decreased with age and was significantly greater in males (p < 0.05); there was no linear correlation between anterior chamber depth and intraocular pressure, and no significant differences were found according to geographic location.Conclusion: Anterior chamber depth is a valuable parameter in diagnosing and treating various ocular conditions. This study provides data on anterior chamber depth specific to the Vietnamese population, contributing to the normative biometric database of the eye, which serves as a reference standard for comparison with pathological cases.
Keywords: Anterior chamber depth.